The effectiveness of the papaya seed (Carica papaya L) for reproductive function of Tilapia, Oreochromis niloticus (Linnaeus, 1758) - Munawar Khalil; Yunidar Yunidar; Mahdaliana Mahdaliana; Munawwar Khalil; Rachmawati Rusydi; Zulfikar Zulfikar (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2019)
Introduction fish in Indonesia has been negatively impact to the water ecology, such as declining in the number of native fish species. Handling the negative impacts of introduced fish can be minimized by reducing fertility rates through the use of plant compound extracts. This study was conducted in May - June 2016 which aimed to assess the effectiveness of the papaya seed flour (Carica papaya L) for the reproductive function of introduction fish Oreochromis niloticus. The research design used in this study was completely randomized design, non-factorial with five treatments and three replications, namely A: control (without giving the flour), B: 40 mg, C: 50 mg, D: 60 mg, E: 70 mg of papaya seeds flour mixing in 100 grams of artificial feed. The fish sample used were 45 mature tilapia fish, 4-5 months old with 200 g in weight for female and 250 gram in weight for male. Parameters measured in this research were feed consumption level, fecundity, fertilization rate, hatching rate and sperm morphological structures. The results of this study indicated that the papaya seed flour gave the multiple effect on the sperm abnormality and decreased the motility level of sperm. Statistical analysis showed that the application of papaya seed flour gave significantly different effect (P <0.05) between treatments on percentage of fertilization level and hatching rate parameters, but showed not significantly different on survival rate parameter where P> 0.05. The lowest sperm motility rate was found in treatment E, which was 00.45